2020
DOI: 10.1002/2211-5463.12907
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in DNA methylation profiles in cancellous bone of postmenopausal women with osteoporosis

Abstract: Abbreviations ACE, angiotensin I-converting enzyme; Ang, angiotensin; COL4A1, collagen type IV alpha 1 chain; GAN11, G protein subunit alpha 11; PLEKHA2, pleckstrin homology domain containing A2; PLEKHB1, pleckstrin homology domain containing B1; PNPLA7, patatin-like phospholipase domain containing 7; PRKCZ, protein kinase C zeta; SCD, stearoyl-CoA desaturase; SYK, spleen-associated tyrosine kinase; TGFB3, transforming growth factor beta 3; TSNAX, translin-associated factor X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…Finally, given the important role of cancellous bone in bone development [ 24 ], the research also focused on EWAS in this tissue derived from patients with postmenopausal osteoporosis. This microarray-based analysis identified 13 genes differently methylated in OP patients, reported in Table 1 to be involved in five important bone-related signaling pathways (calcium; Cyclic Guanosine Phospho-Protein Kinase G, cGMP-PKG; endocytosis; Ras-Associated Protein-1, Rap1; Adenosine Activated Protein Kinase, AMPK) [ 25 ]. Undoubtedly, genome-wide studies represent an invaluable tool in understanding epigenetic mechanisms, although functional validation are needed to confirm novel identified DNA methylation patterns that may contribute to OP development.…”
Section: Dna Methylation Pattern In Osteoporosismentioning
confidence: 99%
“…Finally, given the important role of cancellous bone in bone development [ 24 ], the research also focused on EWAS in this tissue derived from patients with postmenopausal osteoporosis. This microarray-based analysis identified 13 genes differently methylated in OP patients, reported in Table 1 to be involved in five important bone-related signaling pathways (calcium; Cyclic Guanosine Phospho-Protein Kinase G, cGMP-PKG; endocytosis; Ras-Associated Protein-1, Rap1; Adenosine Activated Protein Kinase, AMPK) [ 25 ]. Undoubtedly, genome-wide studies represent an invaluable tool in understanding epigenetic mechanisms, although functional validation are needed to confirm novel identified DNA methylation patterns that may contribute to OP development.…”
Section: Dna Methylation Pattern In Osteoporosismentioning
confidence: 99%
“…Cancellous bone can be affected by osteoporosis earlier than in cortical bone, and a DNA methylation microarray study of the hip cancellous bone in osteoarthritis patients has demonstrated differential methylation [ 44 ]. Zhou et al reported five crucial signaling pathways recently, namely, the signaling pathways of calcium, endocytosis, cyclic guanosine phospho-protein kinase G (cGMPPKG), Rap1, and 5’ adenosine monophosphate-activated protein kinase (AMPK).…”
Section: Dna Methylationmentioning
confidence: 99%
“…Zhou et al reported five crucial signaling pathways recently, namely, the signaling pathways of calcium, endocytosis, cyclic guanosine phospho-protein kinase G (cGMPPKG), Rap1, and 5’ adenosine monophosphate-activated protein kinase (AMPK). All were involved in cancellous weakness in postmenopausal women [ 44 ].…”
Section: Dna Methylationmentioning
confidence: 99%
“…miRNAs participate in osteoporosis research by regulating target genes [15]. On the other hand, some gene methylation is also associated with osteoporosis [16]. Studies speculate that methylation modification of genes in osteoporotic patients may be a compensatory mechanism to combat osteoporosis-related bone loss [17].…”
Section: Introductionmentioning
confidence: 99%